Effect of working hours on behavioral problems in adolescents: A Turkish sample - (:unkn) unknown (UNIVERSITATSVERLAG ULM GMBH, 2007)
Background: This study aimed to compare broad range of behavioral problems and their relations to working status of adolescents in samples of Turkish apprenticeship, technical and high schools. Method: The research was carried out on a total of 899 adolescents aged 15 to 20. The study sample was recruited from three different type of schools (High School, Technical School, Apprenticeship School), located in the city of Zonguldak, Turkey. Two questionnaires were administered to the students. First questionnaire evaluated the adolescents' sociodemographic variables, working status and working durations. Second questionnaire evaluated the behavioral problems namely Youth Self Report (YSR). Results: The majority of adolescents (75.2%) in apprentice programs were working regularly. Compared to adolescents in high school and technical school, adolescent students in apprenticeship programs were found to have higher scores of withdrawn, somatic complaints, depression and anxiety, social problems, delinquent behaviors, internalization and externalization on the YSR. The Total Problems, Internalizing Problems, Somatic Complaints, Anxious/Depressed, Social Problems and Delinquent Behaviors scores of working adolescents were higher than nonworking adolescents. Conclusion: Compared to other schools, adolescents in apprenticeship programs were found to have higher behavioral problems. Longer working hours seems to be associated with withdrawn, somatic complaints, being anxious and depressed, social problems, delinquent behaviors, internalizing and externalization problems. We suggest that it is important to control working conditions of adolescents in order to prevent development of behavioral problems that may lead to several other health problems.
Keywords: behavioral problems; working adolescents; apprenticeship; working hours; occupational mental health; YSR; CBCL; PART-TIME WORK; DRUG-USE; EMPLOYMENT; SCHOOL; CONSEQUENCES; ALCOHOL; ACHIEVEMENT; COMPETENCES; INTENSITY; IMMIGRANT